Deposition and characterization of carbon/carbon composite thin films via FCVA deposition system - Sun, Jian Xun (2016)
The carbon film is first deposited onto a conductive substrate via single-bend filtered cathodic vacuum arc (FCVA) system. By varying the substrate bias and substrate temperature, the microstructure of the amorphous carbon film can change between sp3 rich to sp2 rich. The Nano-Crystalline Graphitic (NCG) carbon can be induced via high ion energy (300eV and above) or high heating temperature (300°C and above). Surface roughness of the film and the film deposition rate are studied by using a surface profiler. Thermal conductivity of the carbon film is measured by using the three-omega thermal measurement technique. The carbon film with high sp3 content has been measured to have a thermal conductivity of 4.3W/mK. The carbon film is also deposited onto a non-conductive substrate via single bend FCVA system with negatively bias mesh. The mesh is required to minimize arcing on non-conductive substrate so that the carbon film with good uniformity can be deposited. The film deposition rate is related to both mesh distance and mesh bias. Experiments show that the deposition rate decreases with the mesh distance while increases with the mesh bias. The film composition is studied by using Raman spectroscopy. Raman results show that the microstructure of the amorphous carbon which is directly formed by neutral carbon atoms can be varied from sp3 rich to sp2 rich through high mesh bias and small mesh distance. Similarly, the Nano-Crystalline Graphitic carbon can be induced by high atom energy.